A Decade of Hydrological Drought in Central-Western Argentina - Rivera, Juan A.; Otta, Sebastián; Lauro, Carolina; Zazulie, Natalia (Frontiers in Water, 2021)
Most of the water used for the development of the main socio-economic activities in Central-Western Argentina (CWA), an arid to semi-arid region, home to most of the Argentinean wine production, relies on surface streamflow from several snow-fed rivers. During the last decade (2010-2020), reduced snow accumulation over the higher elevations of the Andes mountains triggered the occurrence of hydrological drought over CWA, affecting winter tourism, restricting water use for irrigation and domestic use, and leading to socio-political disputes. This study provides a detailed description of the recent hydrological drought conditions through the use of streamflow records from 15 river basins, which were complemented by precipitation, snowpack and water equivalent thickness measurements to provide a comprehensive picture of the water losses over the last decade. Hydrological drought indices derived from the threshold level method and the standardized streamflow index allowed characterizing the unusualness of this dry period in the context of the last 49 years. The hydrological deficit over the last decade highlighted the challenges faced by the water managers to provide water for irrigation in the main agricultural oases, with a likely overexploitation of the groundwater resources to supplement the limited surface runoff. The hydrological drought severity increased since 2017, with record-breaking levels in several basins, particularly during the period between July 2019 and June 2020 for the rivers located between 35° and 36°S. We identified the main hydrological drought impacts in CWA, as well as the need for improved mitigation strategies to cope with current and future drought conditions. We also analyzed the current limitations in terms of snow and groundwater observations, highlighting the necessity for an effective hydrological drought monitoring system, together with an improved forecast of snow accumulation in the headwaters, which can contribute to better regional water management plans.